Benefits Formulation in Construction Projects: An Exploratory Study through a Social Sustainability Perspective. (July 2020) - Goel, Ashish; Ganesh, L.S.; Kaur, Arshinder
Extant project management literature suggests that project benefits management (PBM) can facilitate social sustainability (SS) through benefits formulation for a wider set of project stakeholders. However, empirical evidence regarding the actual extent of SS considerations in benefits formulation is lacking, especially from large developing economies like India. To fill this gap, a SS-centric analysis of PBM plans of 80 construction projects has been conducted using content analysis to identify the benefits targeted at the internal and external stakeholders, viz., workers and project-affected community. The analysis reveals much higher occurrences of benefits for the affected community compared to those relating to the workers. The project proponents have highlighted the social relevance of projects mostly through 'trickle down benefits' – that may possibly accrue to the affected communities due to project investment – as compared to 'co-created benefits' – that empower the affected communities but require a deeper understanding of their needs and aspirations. 'Local employment' and 'local business and economic growth' are the most common benefits across projects. Three areas of improvement have been suggested in the benefits formulation process from a SS perspective – mandating worker-specific benefits, more focus on co-created benefits and specifying numeric measures of benefits along with timelines, to facilitate assessment of actual benefits realization during project implementation and operation phases. This study contributes to research literature on sustainable project management. Its findings offer useful implications for researchers, policymakers and project proponent organizations.